2003
DOI: 10.1256/qj.01.203
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformation of mixed‐phase clouds

Abstract: SUMMARYThe glaciation time of a mixed-phase cloud due to the Wegener-Bergeron-Findeisen mechanism is calculated using an adiabatic one-dimensional numerical model for the cases of zero, ascending, descending and oscillating vertical velocities. The characteristic values of the glaciation time are obtained for different concentrations of ice particles and liquid-water content. Steady state is not possible for the ice-water content/total water content ratio in a uniformly vertically moving mixed-phase parcel. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
146
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(154 citation statements)
references
References 36 publications
8
146
0
Order By: Relevance
“…The second timescale characterizes rate of droplet evaporation and corresponding changes of supersaturation. In this study, as well as later in study by Pinsky et al (2016) (hereafter, Part 3), it will be shown that the characteristic evaporation time is the phase relaxation time τ pr , which determines the rate of change of supersaturation during condensation or evaporation (Mazin, 1968;Korolev and Mazin, 2003) …”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The second timescale characterizes rate of droplet evaporation and corresponding changes of supersaturation. In this study, as well as later in study by Pinsky et al (2016) (hereafter, Part 3), it will be shown that the characteristic evaporation time is the phase relaxation time τ pr , which determines the rate of change of supersaturation during condensation or evaporation (Mazin, 1968;Korolev and Mazin, 2003) …”
Section: Introductionmentioning
confidence: 81%
“…Closed equations describing condensation and/or evaporation in a moving adiabatic air volume were obtained by Pinsky et al (2013). In an unmoving adiabatic volume, evaporation is described by the equation for supersaturation (e.g., Korolev and Mazin, 2003) 1…”
Section: Basic Assumptions and Equationsmentioning
confidence: 99%
“…For instance, upward air motion and turbulent entrainment of air from above the cloud are critical to maintain liquid water in MPCs. Accurate humidity measurements would also be needed to better identify condensational growth of ice crystals (WBF process or direct condensation of water vapor on ice, as described by Korolev, 2007) and resolve the issue of turbulence and mixing at cloud edges and into clouds. All these parameters, along with radiative flux measurements, are of primary importance to constrain our assumptions on the microphysical processes.…”
Section: Discussion On Statistical Vertical Profilesmentioning
confidence: 99%
“…This aerosol indirect effect leads to a longer mixed-phase cloud lifetime, which is opposite the aerosol glaciation indirect effect (Lance et al, 2011). Even more complicated is the coupling of local thermodynamic conditions and large-scale dynamics contributes greatly to the long persistence of mixed-phase clouds (Korolev and Isaac, 2003;Morrison et al, 2012). Bühl et al (2016) estimated ice mass flux at mixed-phase cloud base using ground-based radar measurements and showed that when temperatures are above −15 • C the water depletion due to ice formation is small and the cloud layer is very stable.…”
Section: Introductionmentioning
confidence: 97%